STRATEGIC TYPOLOGY AND ITS CONTEXTUAL ROLE IN SHAPING THE ESG-FIRM VALUE NEXUS - Karina Praadhi Pambudyaningtyas; Mitha Dwi Restuti (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
In the pursuit of long-term survival and growth, firms must strengthen investor relations and secure stakeholder trust to enhance share prices, thereby reflecting greater firm value. Investment decisions today extend beyond financial metrics, incorporating sustainability considerations through the Environmental, Social, and Governance (ESG) framework. To fully capture ESG’s value-creating potential, firms operate within distinct strategic typologies that shape their competitive responses. The prospector typology emphasizes innovation and market exploration, whereas the defender typology focuses on efficiency and market stability. This study examines the influence of ESG performance on firm value, while recognizing strategic typology as a contextual factor in this relationship. Using 639 firm-year observations from Indonesian Stock Exchange–listed firms with ESG scores from Refinitiv Eikon (2014–2024), regression results reveal that ESG performance significantly enhances firm value. This positive association persists across both prospector and defender strategies, highlighting ESG’s universal relevance as a driver of firm value. This research underscores ESG performance as a sources of value creation for firms and highlights the importance of aligning sustainability practices with firms' strategic characteristics, particularly within the context of emerging markets.